2001
DOI: 10.1007/s001670100198
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision technique misses the anatomical femoral anterior cruciate ligament insertion: a cadaver study

Abstract: We examined the arthroscopic appearance of the anterior cruciate ligament (ACL) attachment site on the femur in five fresh-frozen cadaver knees. First, the ACL was cut out, leaving a footprint of ligament-fibers with a length of 2 mm intact. The ACL was consistently found to insert on the lateral wall of the notch. No fibers were found to attach high in the roof of the notch at the 12 o'clock position. Secondly, we tried to reach the anatomical attachment site with a femoral aiming guide through a correctly pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
225
0
14

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 243 publications
(244 citation statements)
references
References 22 publications
5
225
0
14
Order By: Relevance
“…Difficulties placing the femoral tunnel in the ACL footprint using single-incision transtibial tunnel techniques have been reported [5,9,29]. Arnold et al [5] reported the anatomic attachment site of the ACL could not be reached with a femoral aiming guide through a standard tibial tunnel.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Difficulties placing the femoral tunnel in the ACL footprint using single-incision transtibial tunnel techniques have been reported [5,9,29]. Arnold et al [5] reported the anatomic attachment site of the ACL could not be reached with a femoral aiming guide through a standard tibial tunnel.…”
Section: Discussionmentioning
confidence: 99%
“…Arnold et al [5] reported the anatomic attachment site of the ACL could not be reached with a femoral aiming guide through a standard tibial tunnel. The closest position that could be reached was at the margin of the anatomic attachment site, deep and high in the notch [5]. In the current study, we also had difficulty placing the guide pin near the center of the ACL attachment using the transtibial technique in every specimen.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations